“Evaluación in tiro del grado de inhibición del crecimiento microbiano de las recetas caseras utilizadas en el tratamiento de infecciones vaginales en la comunidad nativa de chirikyacu 2014” - Rodriguez Espejo, Yoni Meni (2015)
This research aims to evaluate and recognize the ancestral knowledge of the use of medicinal plants and practice of therapeutic treatment of vaginal discharge, which is a common cause of infections in women worldwide, so it is considered a public health problem today. The methodology included the following: isolating microorganisms from samples of vaginal secretion of patients treated at the health center of Chirikyaku. As for the medicinal plants used in the treatment of vaginal infections, of the 14 referred to in the survey, 6 are commonly known as guayaba, piñon, malba, indano, cordoncillo and pacunga: with which the phytochemical screening was performed. 5 records of consent were also obtained from a total of 15 homemade prescriptions and these five referred to treatment of vaginal infections, 3 of which were chosen for inhibition testing. Results in inhibition of growth of Bacillus sp. Gram-negative and Gram-positive Gandida sp in the diffusion test showed that the three prescriptions had high activity relativa to the positiva control of 96 ° alcohol, from the statistical point of view there was significant difference between the inhibitory effect of each prescription. In the results of the phytochemical screening of the plants listad above are found: alkaloids, tannins, saponins, free steroids, pentacyclic Triterpenes, phenols, pyrogallic tannins, flavones tannins, fixed coumarins, volatile coumarins, Anthraquinones, Flavanoids.